Students’ Perception Toward Politeness and Impoliteness of the Lecturers of English Department at UKI TORAJA - Sushy Sushy (Teaching English as a Foreign Language Overseas Journal, 2017)
This research aimed to find out students’ perception toward Politeness andImpoliteness used by the Lecturers of English Department at UKI Toraja.Theparticipants of this research was the Students of English Department. To determinethe participants, the researcher used incidental sampling. The researchers took 20Students of English department at UKI Toraja as participants. The researcher tookthe data by using questionnaires. It was analyzed by using likert scale. Thequestionnaire that consist of 7 positive statement and 7 negative statement. Theresearcher used descriptive analysis technique to get relative frequency. Based onthe data analysis on the previous part, the researcher conclude that the most of thestudents’ have positive perceptions about politeness and impoliteness of thelecturers of English Department at UKI Toraja, it means that lecturers of Englishdepartment at UKI Toraja are polite.